1995
DOI: 10.3750/aip1995.25.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic fungi growing on the eggs of several species of acipenserid fishes

Abstract: The authors investigated the mycoflora developing on t he eggs of six species of acipenserid fishes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
2
11
0
1
Order By: Relevance
“…As is known, the water of Biała river is more eutrophic than the water of the Dojlidy pond. We observed similar phenomenon examining the straminipilous organisms growing on the eggs of acipenserid fishes (Czeczuga et al, 1995).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…As is known, the water of Biała river is more eutrophic than the water of the Dojlidy pond. We observed similar phenomenon examining the straminipilous organisms growing on the eggs of acipenserid fishes (Czeczuga et al, 1995).…”
Section: Resultssupporting
confidence: 63%
“…Pythium ultimum Trow was found on the eggs of Lepomis macrochirus Raf.,1875 (Scott and O΄ Bier, 1962) and on the sturgeon Acipenser nudiventris Lovetzky,1834 (Czeczuga et al, 1995), and on Tilapia fish (El-Sharouny and Bedran, 1995), and on eggs of Hucho hucho (L.,1758) salmon . Pythium hydnosporum (Mont.)…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, this fungus was found on the eggs of Alosa fallax, and earlier on the eggs of Coregonus albula, Coregonus lavaretus, Esox lucius (cf Czeczuga and Woronowicz 1993), and on the eggs of sturgeon-Acipenser nudiventris ( cf. Czeczuga et al 1995). Pythium debaryanum was first described in the previous century (Hesse 1874) as a soil phytophatogen.…”
Section: Discussionmentioning
confidence: 99%
“…Carrying out the studies on fungi growing on fish eggs (Czeczuga and Woronowicz 1993;Czeczuga 1994;Czeczuga et al 1995, we decided to concentrate on some species of the genus Alosa, whose representatives spawn in riverine waters.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal infection in fish eggs is usually caused by the fungi of the family Saprolegniaceae, including the genera Saprolegnia and Achlya (Wesley and Wolf 1937;Srivastava and Srivastava 1977;Srivastava 1980;Sati 1985;Padmakumar et al 1985;Czeczuga and Woronowicz 1993;Czeczuga et al 1995;Kitancharoen and Hatai 1998). Willoughby and Lilley (1992) reported the first records of Allomyces as a saprophyte on the dead fish in water in Thailand.…”
Section: Introductionmentioning
confidence: 97%